VOLATILIZATION MERCURY (II) INTO MERCURY (0) USING CRUDE ENZYME PRODUCED BY A MERCURY–RESISTANT AZOTOBACTERIA - Zulaika, Enny; Sakinah, Anjar Lulu; Khotimah, Kusnul; Kuswytasari, Nengah Dwianita; Alami, Nurhidayatul; Citrasari, Nita; Sembiring, Langkah; Shovitri, Maya (Acta Scientiae et Intellectus, 2024)
Mercury was poisonous and hazardous heavy metal, even one genus bacteria of Azotobacter was able to grow in a mercury contaminated habitat. This research aim was to select potential mercury resistant Azotobacter which was able to produce an extracellular mercury reductase for reducing toxic ion Hg2+ into a volatile less toxic ion Hg0. The isolates were A1a, A5 and A9 from an urban farming soil in ITS. Their viability under mercury stress was tested individually in an Azotobacter-selective agar each containing 0.1; and 5 mg/L HgCl2. The 24-hours bacterial growth was spectrophotometrically determined at λ600 nm each hour. The crude extracellular mercury reductase produced under 5mg/L dan 10mg/L HgCl2 stress was then extracted followed general method. The enzyme activity was spectrophotometrically measured at 340 nm to detect soluble oxidized NADH in a defined medium for a mercury reductase assay after 12 hours incubation. The viability test showed that those 3 isolates had a similar growth curve pattern; all of them were growing under 0.1; and 5 mg/L HgCl2, even after 12 hours incubation time they were start dying. Anyhow isolate A1a was the slowest growing Azotobacter under particular mercury stress. Enzyme activity tended to decrease over time; isolates A5 and A9 showed a greater enzyme activity than isolate A1a. Under 5mg/L HgCl2 stress, after 30, 60 and 120 minutes, isolate A5 and A9 produced 2.50U, 1.15U and 0.60U enzyme respectively, while under 10mg/L HgCl2 they were 2.70U, 1.44U and 0.7U.